Impact of Ischemic Intra-Conditioning on Power Output and Bar Velocity of the Upper Limbs - Wilk, Michal; Krzysztofik, Michal; Jarosz, Jakub; Krol, Pawel; Leznicka, Katarzyna; Zajac, Adam; Stastny, Petr; Bogdanis, Gregory C. (Frontiers in Physiology, 2021)
Abstract: This study evaluated the effects of ischemic conditioning on power output and bar velocity in the bench press exercise. Ten healthy males (age: 25 ± 2 years; body mass: 92 ± 8 kg; bench press one repetition maximum -1RM: 145 ± 13 kg), took part in two experimental sessions (with and without ischemia), one week apart in random and counterbalanced order. In the ischemic condition, cuffs placed around the upper part of the arms were inflated to 80% of arterial occlusion pressure before each set, while in the control condition there was no blood flow restriction. The exercise protocol included 5 sets of three repetitions each, against a resistance equal to 60% 1RM, with 5 min recovery intervals between sets. There was a main effect of condition for mean power output (MP) and mean bar velocity (MV) (p=0.01), with overall MP being higher in ischemia than in control by 5.6%, ±4.1% (mean, ±90% compatibility limits), a standardized effect size (ES) of 0.51. Overall MV was also higher by 5.5%, ±4.0%, ES = 0.63. Peak power output (PP) and peak bar velocity (PV) were similar in set 1 of the control and ischemia condition (1039 ± 105 vs. 1054 ± 82 W; 684 ± 74 vs. 696 ± 53 W; 1.09 ± 0.07 vs. 1.12 ± 0.09 m/s; 0.81 ± 0.05 vs. 0.82 ± 0.05 m/s, p=0.67 to 0.99, mean ± standard deviation). However, from set 3 onwards (p=0.03 to 0.001), PP and PV were higher in ischemia compared with control, with the highest difference observed in set 5 (10.9%, ±5.9%, ES = 0.73 for PP and 8.6%, ±4.6%; ES = 0.89 for PV). These results indicate that ischemia used before each set of the bench press exercise increases power output and bar velocity and this may be used as performance-enhancing stimulus during explosive resistance training.